2016
DOI: 10.1259/bjr.20160194
|View full text |Cite
|
Sign up to set email alerts
|

Safely prolonging single breath-holds to >5 min in patients with cancer; feasibility and applications for radiotherapy

Abstract: Objective:Multiple, short and deep inspiratory breath-holds with air of approximately 20 s are now used in radiotherapy to reduce the influence of ventilatory motion and damage to healthy tissue. There may be further clinical advantages in delivering each treatment session in only one single, prolonged breath-hold. We have previously developed techniques enabling healthy subjects to breath-hold for 7 min. Here, we demonstrate their successful application in patients with cancer.Methods:15 patients aged 37–74 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 25 publications
3
67
3
Order By: Relevance
“…In addition, the observation that organ motion is more pronounced during the start of breathholding is also reflected in the data from earlier studies [18,24]. They reported a mean diaphragm [24]. So, delaying treatment for a certain amount of time after the start of breath-holding can result in a more stable anatomy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, the observation that organ motion is more pronounced during the start of breathholding is also reflected in the data from earlier studies [18,24]. They reported a mean diaphragm [24]. So, delaying treatment for a certain amount of time after the start of breath-holding can result in a more stable anatomy.…”
Section: Discussionmentioning
confidence: 77%
“…at least 20-30 s). Breath-hold durations of >5 minutes have been shown to be feasible [24,30]. It may also be considered to use breath-holding in combination with a MR-guided linear accelerator system that can visualize tumor motion during irradiation [32,33].…”
mentioning
confidence: 99%
“…Our patients' DIBH durations were 20-30 s, only one patient performed a longer DIBH, therefore a 40-s DIBH acquisition may only be possible in very few selected patients, unless mechanical oxygen enhanced ventilation is applied. 25 Boda-Heggemann et al 15 reported on continuous acquisition of CBCT while the patient's respiration varied between DIBH and FB. They found the method produced a blurred tumour image with additional presence of a ghost tumour, representing the tumour's position in the FB.…”
Section: Discussionmentioning
confidence: 99%
“…Another study using ABC was performed by Zhao et al (2008), with the results showing an average intra-fraction position of the diaphragm of 1.6 mm. Breath-hold treatments at full inspiration combined with breathing of oxygen can increase the fractional time that the beam is on, thereby increasing the delivery efficiency (Bush unpublished, 2003;Romano et al, 2013;Parkes et al, 2016) and, possibly, reducing intra-fraction motion.…”
Section: Residual Motion During Breath-hold Proceduresmentioning
confidence: 99%